The Role of Middle Managers’ Tacit Knowledge in Strategizing: Exploration Through Strategy-as-Practice Lens - Poudel, Dinesh (My University, 2016)
Middle managers and their tacit knowledge widely contribute to the organizational strategy. Yet, strategy research has overlooked diverse set of tacit knowledge that middle managers employ in practice. Particularly, when middle managers work in a social context. Ensuing this notion, the central aim of this study is to identify ‘what’ and understand ‘how’ middle managers use ‘tacit knowledge’ to shape the process of strategizing. Meanwhile, upper management echelon and lower subordinates are taken as a social context i.e. working community, where middle managers socially employ and deploy their tacit knowledge to perform the goal oriented activities. This study is based on strategy-as-practice as a theoretical lens and in particular, activity system framework was used to examine how middle managers and their working community linked together through tacit knowledge that yields strategizing. As a methodological approach, semi-structure interview was conducted with middle managers from two industrial firms. The ‘cards of epitomes’ was used as an interview tool to explore respondents’ tacit knowledge. In this exploratory research inductive approach was adapted and it is cross-sectional in nature. Moreover, within case and cross-case analysis was carried out to identify if there are any similarities and differences in two case companies. The findings suggest that middle managers’ tacit knowledge positively influence their working community and consequently shape strategizing. Most importantly, diverse set of tacit knowledge such as: abstract and concrete; individual and collective; mental, sensual, emotional and practical tacit knowledge were identified. Among all, tacit knowledge that are concrete in nature were the most significant tacit knowledge; similarly, both individual and collective tacit knowledge were also identified to be important at their own stand; finally, mental and practical level of activities were affected mostly.
Keywords: Middle manager; strategizing; tacit knowledge; strategy-as-practice; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master’s Programme in Strategic Business Development|